The impact ringgit fluctuation towards profitability of islamic banks in Malaysia - Suhaily, M. A. M (Opción, 2019)
Profitability of a bank is mostly relying on its financial performance as the ability to leverage operational, investment decisions and strategies to achieve a business’ financial constancy. This study is devoted to examine the selected Malaysian Ringgit factors that bring impact to the bank’s profitability of local Islamic banks in Malaysia. The findings show three independent variables gives positive significant relationship. For that purposes, policymakers should focus on these three variables for standardizing the economic environment to all local Islamic banks that operates in this country.